Metal complexes of an oxatriaza macrocycle containing pyridine - Costa, J (2015)
A new 14-membered oxatriaza macrocycle containing pyridine has been synthesized, 7-oxa-3,11,17-triazabicyclo[11.3.1]heptadeca-1(17),13,15-triene, L-1. The protonation constants of this compound and stability constants of its complexes with the Mn2+ to Zn2+, Cd2+, and Pb2+ were determined by potentiometric methods at 25 degreesC and ionic strength 0.10 mol dm(-3) in KNO3. L-1 presents two high values of protonation constants, and the third is very low. Its overall basicity is low because the three basic centres are in close proximity. Only mononuclear complexes were found, and the stability constants with all the metal ions studied are of the same order as those of the corresponding complexes of the oxatriaza macrocycle L-2 (1-oxa-4,8,12-triazacyclotetradecane), but lower than those of tetraaza macrocycles of similar or lower cavity size. The electronic spectra together with the values of magnetic moments of the cobalt(II) and nickel(II) complexes of L-1 suggest that five co-ordinate species are formed in aqueous solution. The EPR spectroscopy of frozen solutions of the copper(II) complex of L-1 has shown only one species characteristic of rhombic symmetry with elongation of the axial bonds and a d(x2-y2) ground state, and the analysis of the EPR parameters suggests the presence of a bis complex containing two macrocyclic units. The single crystal structure of the complex [(CuLCl)-Cl-1]ClO4 1 was determined. The complex crystallises in the triclinic system, space group P (1) over bar, a = 7.4973(9), b = 9.649(2), c = 12.712(2) Angstrom, beta = 111.02(2), beta = 96.65(1), gamma = 90-11(1)degrees, Z = 2, D-calcd = 1.691 g cm(-3). Final R and R ' values of 0.0578 and 0.1454 for 2603 reflections with I 2 sigma (I) and 0.0782 and 0.1619 for all data were obtained. The complex displays a distorted square pyramidal co-ordination sphere, the three nitrogen atoms of the macrocycle and one chlorine atom determining the basal plane and the apical position occupied by the oxygen atom of the macrocyle. The metal centre is 0.275(2) A away from the N3Cl plane towards to the apical ligand giving rise to a Cu - O bond length of 2.247(4) Angstrom. To achieve this geometric arrangement the oxatriaza macrocycle folds about the line defined by the nitrogen atoms contiguous to the pyridine ring leading to a dihedral angle of 72.2(2)degrees. The single crystal presents a 1-D centrosymmetric supramolecular structure formed by two chains of cations and anions linked by hydrogen bonding via N-H . . .O and C-Hdelta+. . .Odelta-. intermolecular interactions.